Community Empowerment-based Corporate Social Responsibility Program in Panglima Raja Village - W, Willya Achmad (IHSA Institute, 2023)
Corporate social responsibility is an obligation that must be fulfilled by every company so that it can have a good impact on the community in the surrounding environment, PT Syams Arief Shumun is a subsidiary engaged in the processing of oil palm and natural resource processing in Kampar Regency. This company has 3 community-based CSR programs, first, Economic Empowerment. Second, Environmental Empowerment and Third, Social Empowerment. This study uses a qualitative approach with descriptive methods and data collection through observation, interviews and literature studies related to CSR and community empowerment, informant determination techniques through purposive sampling and data analysis using data triangulation.